Heat dissipative Pb-free bonding technology using Al-rich Zn/Al/Zn clad solder*. Issue 11 (2nd November 2017) - Yamaguchi, Takuto; Tohei, Tomotake; Ikeda, Osamu; Hata, Shohei; Oda, Yuichi; Kuroki, Kazuma; Kuroda, Hiromitsu; Hirose, Akio
Abstract: Al-rich Zn/Al/Zn clad solder were developed as Pb-free solder for a die-attachment. The Zn/Al/Zn clad solder was produced by clad rolling of Zn and Al strips in order to prevent Al from oxidation and improve wettability. The Zn/Al/Zn clad solder was melted at 382°C after solid-state interdiffusion of the Zn and Al layers. Bonding was successfully achieved with bonding pressure of a few kilopascals. Thermal cycle life of Invar-to-Cu substrate joint using the Zn/Al/Zn clad solder was longer than that of Pb-Sn-Ag solder. No Kirkendall voids were observed in the vicinity of the bonded interface after ageing at 250 °C for 1000 h.